THE URGENCY OF INDONESIA'S DEFENCE DIPLOMACY IN RESPONDING TO THE SOUTH CHINA SEA CONFLICT - Farid, Muchammad; Junnah, Azima Raudhalia; Ambarwati, Ambarwati (Universitas Pendidikan Muhammadiyah Sorong, 2023)
Geopolitical conflict in the South China Sea is a complex and complicated issue, involving several countries that are divided into claimant states and non-claimant states. Claimant states refer to countries such as China, Taiwan, the Philippines, Vietnam, Malaysia, and Brunai Darusalam that claim territory in the South China Sea, while Indonesia is included in the non- claimant state category. This is due to the development of problems that continue from year to year, while the geographical position and the South China Sea route have strategic importance. As the world's maritime axis, Indonesia must maintain a neutral position and play a role in achieving peace in the conflict by utilising opportunities in the international context. This research uses a qualitative method with descriptive analysis, by collecting data through literature sources such as books, journals, and magazines. The focus of this research is to understand the role and benefits of Indonesia's defence diplomacy in handling geopolitical conflicts in the South China Sea, both on a national and international scale. The results show that Indonesia plays an active role in realising world peace through conflict resolution in the South China Sea, by promoting peaceful resolution based on UNCLOS. In this process, Indonesia gained benefits such as the maintenance of maritime sovereignty, increased regional security and stability, strengthened bilateral relations, and became a promoter in providing peaceful solutions in accordance with international law.